1995
DOI: 10.3109/08958379509029097
|View full text |Cite
|
Sign up to set email alerts
|

Labeling Rat Alveolar Macrophages with Fluorescent Microspheres

Abstract: I Alan HodgsonNational Radiological Protection Board, Chilton, Oxfordshire, United Kingdom Rats were exposed for various periods (5, 20, 60, and 720 min) to an aerosol of fluorescent polystyrene microspheres (FPM) with nominal diameter 7.07 p m . All the animals were killed 40 h later and the lungs were lavaged 70 times with physiological saline. Washings 7-2 and 3-70 were combined. The numbers of alveolar macrophages (AM) recovered by lavage were measured with a Coulter counter. Cytospin slides of cells in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Another possibility is that heavily loaded AM are more readily recovered by lavage. With the rat, there appear to be much smaller differences in the characteristics of macrophages recovered in the initial and later lung washes (Morgan et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another possibility is that heavily loaded AM are more readily recovered by lavage. With the rat, there appear to be much smaller differences in the characteristics of macrophages recovered in the initial and later lung washes (Morgan et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…When lavage was used to recover cells from the mouse lung following inhalation exposure to monodisperse fluorescent polystyrene particles (FP) it was found that AM recovered in washes 1 and 2 had a somewhat higher labeling index (LI, proportion of AM containing one or more FP) than AM recovered in subsequent washes and that this difference persisted until at least 8 days after exposure (Morgan et al, 1991). However, more recent studies of the recovery of macrophages from the rat lung following inhalation of FP showed that differences in the labeling index of AM recovered in the initial and subsequent lung washes were not significant (Morgan et al, 1995).…”
mentioning
confidence: 80%
See 1 more Smart Citation